Inovasi Pembelajaran Untuk Mewujudkan Peserta Didik Berakhlak Mulia Di UPT SDN 04 Lunang - Weni Yulastri; Mujiati; Novi Zaini; Kartini; Halimatul Mahmudah; Gusmal Hendra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to examine the implementation of learning innovations in fostering students’ noble character at the elementary school level. Using a qualitative descriptive approach, the research was conducted at UPT SDN 04 Lunang with participants consisting of classroom teachers and students directly involved in character-based learning practices. Data were collected through classroom observations, semi-structured interviews, and documentation, and analyzed using interactive data analysis techniques. The findings indicate that learning innovations are implemented through the integration of moral values into thematic learning, reflective learning activities, experiential learning based on the surrounding environment, habituation of learning ethics, the use of exemplary stories, character-based assessment, and the strengthening of school culture. These innovations contribute to the development of students’ moral awareness, responsibility, discipline, and social attitudes. The study concludes that contextual and holistic learning innovations play a strategic role in achieving national education goals by balancing cognitive development with character formation at the elementary education level.